Spotlight on Practice - Martin, Heather (Operating Room Nurses Association of Canada Journal, 2024)
Did you know… ORNAC does not set, or regulate, scope of practice and role for perioperative nurses of any designation working in operating rooms across Canada? As the professional association for perioperative nurses, ORNAC supports your practice with evidence-informed, best practice recommendations through education, advocacy, and through the publication of the ORNAC Standards and Guidelines.